Effects of the endosperm of tara seeds and powder of agave Americana leaves on body weight and intestinal transit time in Holtzman rats - Vilcanqui-Pérez, Fulgencio (2018)
Objective. To evaluate the effects of endosperm of tara seeds (ETS) and powder of Agave americana leaves (AAL) on body weight and intestinal transit time in Holtzman rats. Materials and Methods. Twenty-five male Holtzman rats, individually caged, and distributed into five groups were fed for 21 days with one of the following treatments: T1, diet with 6% alpha cellulose (Control); T2, diet with 6% ETS; T3, diet with 6% AAL; T4, diet with 10% ETS; and T5, Diet with 10% AAL. Feed intake, body weight gain, apparent digestibility of fat, characteristics of feces (fat content, weight, moisture, volume, and pH) and intestinal transit time were recorded. One-way analyses of variance (ANOVA) were performed, as well as Tukey’s multiple means comparison. Results. Diets with 6% and 10% of ETS resulted in a reduction of feed intake, apparent digestibility of fat, and fecal pH, and said results had an effect in the reduction of body weight gain of 37.0% (p=0.008) and 50.9% (0.001), compared with the control diet. The diet with 10% of AAL powder reduced the intestinal transit time from 642 min (control) to 532 min (p=0.242). Conclusions. Diets containing EST regulated body weight gain, while the diet with AAL powder had no effects on the intestinal transit time in rats. © 2018, Instituto Nacional de Salud. All rights reserved.